1986
DOI: 10.1042/bj2360665
|View full text |Cite
|
Sign up to set email alerts
|

Photoaffinity labelling of a nitrobenzylthioinosine-binding polypeptide from cultured Novikoff hepatoma cells

Abstract: Site-specific binding of nitrobenzylthioinosine (NBMPR) to plasma membranes of some animal cells results in the inhibition of the facilitated diffusion of nucleosides. The present study showed that nucleoside transport in Novikoff UA rat hepatoma cells is insensitive to site-saturating concentrations of NBMPR. Equilibrium binding experiments demonstrated the presence of high-affinity sites for NBMPR in a membrane-enriched fraction from these cells. In the presence of uridine or dipyridamole, specific binding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1986
1986
1997
1997

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…In some cell lines, such as Novikoff hepatoma cells (Plagemann & Wohlhueter, 1984a) and Walker 256 carcinosarcoma cells Belt & Noel, 1985) high concentrations of NBMPR (1 tXM) have little effect on saturable nucleoside transport. Consistent with this observation is the finding that these cells also lacked high-affinity sites for NBMPR Plagemann & Wohlhueter, 1984a), although such sites are present on cells of another Novikoff hepatoma cell line (Novikoff-UA cells) where nucleoside transport is also not inhibited by nanomolar concentrations of NBMPR (Gati et al, 1986). The molecular properties of these NBMPR binding sites on Novikoff-UA cells are different from those on cells where NBMPR inhibits transport with a high sensitivity.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…In some cell lines, such as Novikoff hepatoma cells (Plagemann & Wohlhueter, 1984a) and Walker 256 carcinosarcoma cells Belt & Noel, 1985) high concentrations of NBMPR (1 tXM) have little effect on saturable nucleoside transport. Consistent with this observation is the finding that these cells also lacked high-affinity sites for NBMPR Plagemann & Wohlhueter, 1984a), although such sites are present on cells of another Novikoff hepatoma cell line (Novikoff-UA cells) where nucleoside transport is also not inhibited by nanomolar concentrations of NBMPR (Gati et al, 1986). The molecular properties of these NBMPR binding sites on Novikoff-UA cells are different from those on cells where NBMPR inhibits transport with a high sensitivity.…”
Section: Introductionsupporting
confidence: 61%
“…The molecular properties of these NBMPR binding sites on Novikoff-UA cells are different from those on cells where NBMPR inhibits transport with a high sensitivity. Photoaffinity labeling studies with [3H]NBMPR have demonstrated that the molecular weight of the human erythrocyte and the $49 mouse lymphoma NBMPR binding polypeptide, as revealed by SDS-gel electrophoresis, is 65,000 to 45,000, but 80,000 to 72,000 for Novikoff-UA cells (Wu et al, 1983a,b;Young et al, 1984;Gati et al, 1986). Thus, the relationship of the NBMPR binding sites on Novikoff-UA cells with the nucleoside transport mechanism is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular-mass markers (BSA, 66 kDa; ovalbumin, 45 kDa; glyceraldehyde-3-phosphate dehydrogenase, 36 kDa; carbonic anhydrase, 29 kDa; trypsinogen, 24 kDa; trypsin inhibitor 20 kDa; and lactalbumin, 14 kDa) and proteins present in samples were detected with Coomassie Blue. For analysis of photolabelled polypeptides, radioactivity was measured in a liquid-scintillation system after extraction of 2 mm slices of the gel lanes into a solution of 3 % Protosol in Econofluor [37].…”
Section: Sds/page and Immunoblottingmentioning
confidence: 99%
“…Transporters of the es type are widely distributed in different cell types and tissues, bind NBMPR reversibly, and can be covalently radiolabeled with [ 3 H]NBMPR by exposure of the transporter-ligand complex to UV light (14). The es and ei nucleoside transporters are under independent genetic control and are produced either singly or together in different cell types and tissues (15)(16)(17)(18)(19)(20)(21). Both have a broad substrate selectivity for purine and pyrimidine nucleosides.…”
mentioning
confidence: 99%